Task Progression Strategies. (3rd September 2017) - Ryan, Stu; Baxter, Karen; Waller, Cassandra
Abstract : Teachers are often challenged with trying to determine the most effective way of developing task progression. Following developmentally appropriate steps that will lead to effective skill development can facilitate student learning. Using the acronym NEMWPT - which stands for No equipment, Equipment, Movement, Wall work, Partners, and Teams - may aid the teacher in following appropriate progressions. This article explains how these key wordscan help teachers develop appropriate task progressions to ensure student success.